The metabolic map into the pathomechanism and treatment of PGM1-CDG - Radenkovic, Silvia; Himmelreich, Nastassja; Thiel, Christian (American journal of human genetics, 2019)
Phosphoglucomutase 1 (PGM1) encodes the metabolic enzyme that interconverts glucose-6-P and glucose-1-P. Mutations in PGM1 cause impairment in glycogen metabolism and glycosylation, the latter manifesting as a congenital disorder of glycosylation (CDG). This unique metabolic defect leads to abnormal N-glycan synthesis in the endoplasmic reticulum (ER) and the Golgi apparatus (GA). On the basis of the decreased galactosylation in glycan chains, galactose was administered to individuals with PGM1-CDG and was shown to markedly reverse most disease-related laboratory abnormalities. The disease and treatment mechanisms, however, have remained largely elusive. Here, we confirm the clinical benefit of galactose supplementation in PGM1-CDG-affected individuals and obtain significant insights into the functional and biochemical regulation of glycosylation. We report here that, by using tracer-based metabolomics, we found that galactose treatment of PGM1-CDG fibroblasts metabolically re-wires their sugar metabolism, and as such replenishes the depleted levels of galactose-1-P, as well as the levels of UDP-glucose and UDP-galactose, the nucleotide sugars that are required for ER- and GA-linked glycosylation, respectively. To this end, we further show that the galactose in UDP-galactose is incorporated into mature, de novo glycans. Our results also allude to the potential of monosaccharide therapy for several other CDG.
Gesehen am 03.07.2019